(untitled) (Scientific journal of the Fergana State University, 2023)
Isotherm, differential heats, entropy and thermo kinetics of carbon dioxide adsorption in СаА (М-22) élite were measured at 303K. The detailed mechanism of carbon dioxide adsorption in СаА (М-22) zeolite from zero filling to saturation was discovered. The adsorption isotherm was quantitatively reproduced by VOM theory equations.